Strategi Pemanfaatan Papan Interaktif Digital (PID) untuk Penguatan Literasi Siswa SDN 1 Ciherang Kecamatan Pasawahan Kabupaten Purwakarta - Bubun Munawar Burhanudin; R. Riana Yuhansyah; Ai Yuni Haryanai; Waska Warta (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the strategy for utilizing the Digital Interactive Board (DIB) in classroom learning to strengthen students' literacy and to analyze its impact on students' literacy skills at SDN 1 Ciherang, Pasawahan District, Purwakarta Regency. This study employed a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis involving the principal, teachers, and students. Data trustworthiness was ensured through source, technique, and time triangulation, prolonged engagement, and *member checking*. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that the DIB utilization strategy was implemented through digital literacy-based lesson planning, multimedia integration, interactive and participatory learning, and digital literacy-based assessment. The use of the DIB enhanced students' reading interest, reading comprehension, learning engagement, and digital literacy skills. However, its implementation still faced several challenges, including teachers' limited competence in operating the DIB, unstable internet connectivity, and the need for continuous professional development. With systematic planning and implementation, the Digital Interactive Board (DIB) has proven to be an effective learning medium for strengthening literacy and improving the quality of learning in elementary schools.